2011
DOI: 10.1016/j.biopsych.2011.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Brain Change in Schizophrenia: A Prospective Longitudinal Study of First-Episode Schizophrenia

Abstract: Background Schizophrenia has a characteristic onset during adolescence or young adulthood but also tends to persist throughout life. Structural magnetic resonance studies indicate that brain abnormalities are present at onset, but longitudinal studies to assess neuroprogression have been limited by small samples and short or infrequent follow-up intervals. Methods The Iowa Longitudinal Study is a prospective study of 542 first-episode patients who have been followed up to 18 years. In this report, we focus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
264
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 328 publications
(302 citation statements)
references
References 50 publications
30
264
2
3
Order By: Relevance
“…In accordance with this hypothesis, dynamic changes in brain morphology and glutamate signaling have also been reported in recent onset schizophrenia cases and subjects in the prodromal stages of schizophrenia (35,36). In this study, by using two-photon spine imaging, we demonstrated that administration of a PAK inhibitor FRAX486 in late adolescence is sufficient to block deteriorating spine loss and effective in preventing an adult behavioral deficit associated with schizophrenia.…”
Section: Discussionsupporting
confidence: 82%
“…In accordance with this hypothesis, dynamic changes in brain morphology and glutamate signaling have also been reported in recent onset schizophrenia cases and subjects in the prodromal stages of schizophrenia (35,36). In this study, by using two-photon spine imaging, we demonstrated that administration of a PAK inhibitor FRAX486 in late adolescence is sufficient to block deteriorating spine loss and effective in preventing an adult behavioral deficit associated with schizophrenia.…”
Section: Discussionsupporting
confidence: 82%
“…Structural neuroimaging studies indicate that persons with schizophrenia show prominent progressive brain changes at this time. For example, Andreasen and colleagues 1 recently reported on the largest longitudinal study to date looking at brain volume changes over time in a cohort of patients with schizophrenia who had a mean age at first episode of 25 years. They found decreases in multiple grey and white matter regions, and these changes were most pronounced early (2 yr) after intake for the first episode of psychosis.…”
Section: Patricia Boksa Phdmentioning
confidence: 99%
“…[15][16][17] In a more homogeneous sample of patients with firstepisode schizo phrenia, Andreasen and colleagues 18,19 found progressive grey and white matter loss in multiple regions over time related to the severity of psychotic symptoms, relapse duration and anti psychotic treatment intensity. The presence and persist ence of negative symptoms in patients with schizophrenia and related psychoses is also associated with abnormalities in cortical thickness 20 and white matter, 21,22 cognitive deficits, and poor functional and vocational outcomes.…”
Section: Structural Neuroimagingmentioning
confidence: 99%